Substrate Fertilization Technologies forthe Production of Juçara Seedlings for Ornamental Purposes - De Bernardi, Ariana; Brunetti , Gianluca; Vischetti, Costantino; Júnior, Djalma Roecker; Favretto, Eder; Rossa, Uberson Boaretto; Erhardt, Deise Schaiane (Revista da Sociedade Brasileira de Arborização Urbana, 2025)
The sustainable management of forest resources, the high demand for ecological restoration and the productive and ornamental potential of Euterpe edulis make it a key species for the Atlantic Forest conservation. The production of quality seedlings of native species stands out among the propagation strategies. Different products and processes are emerging and being incorporated into the agricultural substrates used by forest nurseries. Three fertilization technologies were tested for the production of Euterpe edulis seedlings: Controlled-Release Fertilizer (CRF), agro-industrial organic compost (FCO) and bokashi (FBO) in four different doses. The experiment used was completely randomized with four replications of thirteen treatments and nine plants as a sample unit, being evaluated at 270 days. The development was measured through the variables shoot height, stem diameter, aboveground fresh matter, and total dry matter, root dry matter, total dry matter. From these, seedling quality indices, stem height and diameter ratio, Dickson quality index and maximum technical efficiency dose were calculated. It was observed that E. edulis seedlings responded positively to the use of CRF and to the use of FCO, however, they did not present satisfactory results for FBO under the tested conditions. The maximum technical efficiency dose found for the FCO was 167.36 Kg.m-3. For CRF a dose of at least 12 Kg.m-3 can be recommended.